2020
DOI: 10.1245/s10434-020-09100-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Borderline Resectability in Pancreatic Head Cancer on Patient Survival: Biology Matters According to the New International Consensus Criteria

Abstract: Background International consensus criteria (ICC) have redefined borderline resectability for pancreatic ductal adenocarcinoma (PDAC) according to three dimensions: anatomical (BR-A), biological (BR-B), and conditional (BR-C). The present definition acknowledges that resectability is not just about the anatomic relationship between the tumour and vessels but that biological and conditional dimensions also are important. Methods Patients’ tumours were retrospectively defined borderline resectable according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…In contrast to studies performed in resectable pancreatic cancer, 13 , 14 , 27 , 28 , 29 , 30 , 31 baseline CA 19-9 levels (using established cut-off levels such as 500 or 1000 U/ml) were neither prognostic (for OS) nor predictive (for R0 resection) in this prospective LAPC trial after multiagent ICT. The two other prospective randomized trials in LAPC using less intensive ICT with or without CRT reported conflicting results about the prognostic role of baseline CA 19-9, 2 , 32 while other prospective trials in LAPC using multiagent ICT with nab-paclitaxel/gemcitabine 7 or FOLFIRINOX 8 did not analyze the prognostic and predictive role of baseline CA 19-9.…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast to studies performed in resectable pancreatic cancer, 13 , 14 , 27 , 28 , 29 , 30 , 31 baseline CA 19-9 levels (using established cut-off levels such as 500 or 1000 U/ml) were neither prognostic (for OS) nor predictive (for R0 resection) in this prospective LAPC trial after multiagent ICT. The two other prospective randomized trials in LAPC using less intensive ICT with or without CRT reported conflicting results about the prognostic role of baseline CA 19-9, 2 , 32 while other prospective trials in LAPC using multiagent ICT with nab-paclitaxel/gemcitabine 7 or FOLFIRINOX 8 did not analyze the prognostic and predictive role of baseline CA 19-9.…”
Section: Discussioncontrasting
confidence: 96%
“…Inoue et al [ 25 ] reported that NAT with gemcitabine and nab-paclitaxel improved downstaging of the tumor and allowed patient selection. Anger et al [ 26 ] investigated the role of NAT in different types of borderline PDAC according to international consensus criteria. Their results showed that PDAC patients with biological (borderline resectable-B) have a relatively poor prognosis and should be considered for multimodal NAT.…”
Section: Nat For Borderline and Unresectable Pdacmentioning
confidence: 99%
“…In addition to being prognostic factors, biological and conditional markers are considered crucial in determining BRPDAC surgical outcomes. CA19‐9 level during preoperative treatment has been shown to predict postoperative outcomes 35,49–53 . Barnes et al 54 analyzed 185 BPRDAC patients who received NCRT (FOLFIRINOX or gemcitabine with nab‐paclitaxel) and reported an MST of 46 months in patients whom normalization of CA19‐9 level was achieved after the completion of NCRT.…”
Section: Resectability Criteria and Corresponding Optimal Treatment Smentioning
confidence: 99%